Inovasi Pariwisata Syariah di Indonesia: Analisis Fatwa MUI No. 108/MUI-DSN/X/2016 - Fahrur Ulum (TSAQAFAH, 2019)
AbstractThis study answers the problem of sharia tourism innovation in Indonesia which is carried out with constant reference to Fatwa MUI No. 108/MUI-DSN/X/2016 about Guidelines for Organizing Sharia-Based Tourism. The method used is descriptive qualitative, the type of literature. Research results show that Fatwa MUI No. 108/MUI-DSN/X/2016 has regulated most aspects of sharia tourism in Indonesia. However, there are several aspects that have not been regulated in more detail, such as the issue of sharia tourism promotion, prevention of child sexual exploitation and community economic empowerment in sharia tourism. Sharia tourism innovation opportunities are still open to the issue of creative industries, sharia transportation, sharia tourism education institutions, halal logos, and sharia logos, and product management and sharia tourist attraction capacity. Innovation in sharia tourism in Indonesia can be carried out constantly with reference to Fatwa MUI No. 108/MUI-DSN/X/2016 because the fatwa is the guidelines for implementing sharia tourism in Indonesia. It is recommended that the government formally issue regulations that are capable of supporting implementation to Fatwa MUI No. 108/MUI-DSN/X/2016. For sharia tourism businesses, they should continue to innovate and continue to pay attention to the various regulations contained in the fatwa, especially on the contracts that have been established in various activities in implementing the sharia tourism business.Keywords: innovation, sharia tourism, fatwa MUI.AbstrakPenelitian ini menjawab permasalahan tentang inovasi pariwisata syariah di Indonesia yang dilakukan dengan tetap merujuk pada Fatwa MUI No. 108/MUI-DSN/X/2016 tentang Pedoman Penyelenggaraan Pariwisata Berdasarkan Prinsip Syariah. Metode yang digunakan adalah deskriptif kualitatif, jenis literature. Hasil research menunjukkan bahwa Fatwa MUI No. 108/MUI-DSN/X/2016 telah mengatur sebagian besar aspek pariwisata syariah di Indonesia. Namun ada beberapa aspek yang belum diatur secara lebih detail, misalnya persoalan promosi pariwisata syariah, pencegahan eksploitasi seksual anak dan pemberdayaan ekonomi masyarakat pada pariwisata syariah. Peluang inovasi pariwisata syariah masih terbuka pada persoalan industri kreatif, transportasi syariah, lembaga pendidikan pariwisata syariah, logo halal dan logo syariah, serta managemen produk dan kapasitas daya tarik wisata syariah. Inovasi pariwisata syariah di Indonesia dapat dilakukan dengan tetap merujuk pada Fatwa MUI No. 108/MUI-DSN/X/2016 karena fatwa tersebut merupakan rambu-rambu penyelenggaraan pariwisata syariah di Indonesia. Disarankan agar pemerintah mengeluarkan peraturan yang mampu menunjang implementasi fatwa MUI No. 108/MUI-DSN/X/2016. Bagi pelaku bisnis pariwisata syariah, hendaknya terus berinovasi dan tetap memperhatikan berbagai peratuan yang ada dalam fatwa tersebut terutama pada akad yang telah ditetapkan dalam berbagai aktifitas pelaksanaan bisnis pariwisata syariah.Kata kunci: inovasi, pariwisata syariah, fatwa MUI